Impact on quality of life of removable partial denture wearers after 2 years of use - Alessandra Oliveira Barreto; Luana Maria Martins de Aquino; Ana Rafaela Luz de Aquino; Ângelo Giuseppe Roncalli; Bruna Aguiar do Amaral; Adriana da Fonte Porto Carreiro (Universidade Estadual de Campinas, 2015)
The use of clinical indicators of satisfaction (OHIP) can be applied to evaluate the impact of denture use on patient quality of life, since dental problems and disorders interfere in the normal life of individuals. Aim: This study aimed at evaluating the satisfaction level of patients rehabilitated with removable partial dentures (RPD) after 2 years of use. Methods: An observational study was carried out on 28 patients with a mean age of 45 years, treated with RPD at the Department of Dentistry of the Federal University of Rio Grande do Norte in 2005. Patients signed informed consent and answered the Oral Health Impact Profile (OHIP) questionnaire on three occasions: prior to rehabilitation and at 3 months and 2 years of denture use. Repeated-measures ANOVA was applied for data analysis. Results: A difference was found between data obtained at the moment of fitting and three months after denture use (p<0.001). However, no variation was observed when comparing data from 3 months and 2 years of use (p>0.05). The variables of gender and age did not interfere in the result (p>0.05). Conclusions: The degree of patient satisfaction after RPD installation was significant at the moment of fitting and 3 months after denture use, but no significant difference was found between 3 months and 2 years of denture use.